Enrique J. Celaya : forjador / Etelvino González López ; [prólogo de Enrique Moral Sandoval] - Celaya Pérez, Enrique J. (1871-1950) Moral Sandoval, Enrique; González López, Etelvino (1937-) (Memorias de Asturias ; 7)
Ded. autógraf. del autor a la FPI